Duḥsamaẏera dinaguli - Māmuna, Munatāsīra, 1951- (Ḍhākā : Māolā Brādārsa, 2010)
Articles on the political conditions from 2001 to 2008 in Bangladesh.
In Bengali.
Includes bibliographical references.
Keywords: Bangladesh -- Politics and government -- 1971-; Political crimes and offenses; Politics and government; Bangladesh; Since 1971; Political crimes and offenses -- Bangladesh